Paracetamol – An old drug with new mechanisms of action. (4th September 2020) - Przybyła, Grzegorz W.; Szychowski, Konrad A.; Gmiński, Jan
Abstract: Paracetamol (acetaminophen) is the most commonly used over‐the‐counter (OTC) drug in the world. Despite its popularity and use for many years, the safety of its application and its mechanism of action are still unclear. Currently, it is believed that paracetamol is a multidirectional drug and at least several metabolic pathways are involved in its analgesic and antipyretic action. The mechanism of paracetamol action consists in inhibition of cyclooxygenases (COX‐1, COX‐2, and COX‐3) and involvement in the endocannabinoid system and serotonergic pathways. Additionally, paracetamol influences transient receptor potential (TRP) channels and voltage‐gated Kv7 potassium channels and inhibits T‐type Cav3.2 calcium channels. It also exerts an impact on L‐arginine in the nitric oxide (NO) synthesis pathway. However, not all of these effects have been clearly confirmed. Therefore, the aim of our paper was to summarize the current state of knowledge of the mechanism of paracetamol action with special attention to its safety concerns. Abstract : Hypothetical scenario of paracetamol action in central nervous system (CNS) and liver. 2‐AG, 2‐arachidonoylglycerol; 5‐HT, 5‐hydroxytryptamine receptor (serotonin receptor); AM404, N‐arachidonoylphenolamine; CB1, cannabinoid receptor type 1; CNS, Central Nervous System; FAAH, fatty amide hydrolase; NAPQI, cN‐acetyl‐p‐benzoquinoneimine; p‐BQ, p‐benzoquinone; PAG, periaqueductal gray; PNS, peripheral nervous system; RVM, rostral ventromedial medulla; TRPA1, transient receptor potential subfamily ankyrin 1; TRPV1, transient receptor potential subfamily vanilloid‐1.